PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN METODE DRILL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA BERBASIS HOTS - Putri Aruan, Andri Zainal, Ulfa Nurhayani, Tuti Sriwedari, Roza Thohiri (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
Student learning activities and learning outcomes are key indicators of the success of the learning process, particularly in Higher Order Thinking Skills (HOTS) based learningwhich requires critical, analytical, and evaluative thinking skills. This study aims to describe the effectiveness of implementing a Problem-Based Learning (PBL) model supplemented by drill methods in enhancing student learning activities and outcomes based on HOTS in the topic of adjusting journals. This study employed the Classroom Action Research method, conducted over two cycles. Each cycle consisted of two sessions, each comprising four stages: planning, action, observation, and reflection. The research subjects were 33 students in Class XI AKL 2 at SMK Negeri 13 Medan. Research data were collected through interviews, observations, tests, and documentation. The results of the study indicate that HOTS-based learning activities increased from 61% in Cycle I to 80% in Cycle II. Additionally, student learning outcomes improved, with the classical mastery rate rising from 63.64% in Cycle I to 100% in Cycle II, in accordance with the established mastery criteria. Thus, it can be concluded that the implementation of the Problem Based Learning model supported by the drill method is effective in improving students HOTS-based learning activities and outcomes.